AGRICULTURE OF KAZAKHSTAN: LEGAL FORMS AND THEIR ECONOMICS (Journal of Economic Research & Business Administration, 2017)
In this article, organizational and legal forms existing in the agricultural sector of Kazakhstan were studied and their comparative analysis was carried out.The purpose of the article is to identify the most widespread organizational and legal form of entrepreneurship in agriculture, and also to analyze the economic efficiency indicators by entities categories. In agriculture of Kazakhstan small enterprises predominate, the age of many enterprises is 11-20 years. In the context of the categories of management agricultural enterprises, house holdings and farms the last one dominates. The number of farms increased during the years of independence by 545 times, whereas agricultural enterprises only by 3.4 times. The spread of this particular form of organization for agricultural production was promoted by state policy, tax breaks in the form of a special tax regime. Agricultural enterprises are more productive than others in the production of milk, eggs, meat, rye and oats, farms- for the production of barley, corn, soybeans, rapeseed and flaxseed flax, and house holdings in offspring.